Porous hollow Ag/Ag2S/Ag3PO4 nanocomposites as highly efficient heterojunction photocatalysts for the removal of antibiotics under simulated sunlight irradiation. (July 2021) - Alshamsi, Hassan Abbas; Beshkar, Farshad; Amiri, Omid; Salavati-Niasari, Masoud
Abstract: Antibiotic pollutants are a serious and growing threat to human health and the environment that efficient measures must be taken to eliminate them. Here, we report the facile fabrication of porous hollow Ag/Ag2 S/Ag3 PO4 heterostrucutres for efficient photocatalytic degradation of tetracycline under simulated sunlight irradiation. The morphology manipulation and hetero-nanocomposites construction through a coprecipitation-refluxing approach were applied to enhance the photocatalytic performance of the Ag/Ag2 S/Ag3 PO4 products. The photodegradation outcomes indicated that the heterojunction Ag/Ag2 S/Ag3 PO4 photocatalyst with a suitable band gap energy of 2.17 eV, has better degradation performance (∼95%) than individual Ag2 S and Ag3 PO4 structures after 120 min of simulated sunlight irradiation, even after five recycles. The good photocatalytic activity of Ag/Ag2 S/Ag3 PO4 nanocomposites could be mainly attributed to the unique hierarchical architectures, promoted visible-light harvesting, reduced a recombination and boosted separation of electron-hole pairs originated from the as-formed heterojunctions. Moreover, we proposed a photocatalytic degradation mechanism based on the radical scavenging results, which disclosed that the O2 − and OH species perform essential tasks for the photodegradation of antibiotics by Ag/Ag2 S/Ag3 PO4 nanocomposites. Graphical abstract: Image 1 Highlights: The Ag/Ag2 S/Ag3 PO4 heterojunction nanocomposite was fabricated by coprecipitation-refluxing. The Ag/Ag2 S/Ag3 PO4 as an efficient visible-light driven photocatalyst for the antibiotic removal application. Morphology engineering of the hierarchical microspheres was performed by controlling the reaction conditions. Excellent photocatalytic degradation of tetracycline as model antibiotic was achieved under simulated sunlight irradiation. A dependable degradation mechanism for the superior photocatalytic performance was explained.